А NEWLY DISCOVERED FIRST EDITION FROM THE YEAR 1678 OF FIFTY QUESTIONS TAKEN FROM THE HOLY SCRIPTURES OF BOTH TESTAMENTS AND SCIENTIFICALLY EXPLAINED IN THE SPIRIT OF THE SUBTLE DOCTOR JOHN DUNS SCOTUS BY FATHER MARKO PEIACHEVICH - Yanko Dimitrov (Езиков свят)
The article examines a hitherto unknown edition of the theological-philosophical text of Marko Peiachevich, a Bulgarian Catholic priest from the end of the 17th and the beginning of the 18th century. The work in question, which is a short philosophical-theological treatise in the spirit of John Duns Scotus, was previously known in an edition of 1679, dedicated to the secretary of the Sacred Congregation for the Propagation of the Faith, Urbano Cerri, and printed in Prague. The newly discovered edition was printed a year earlier in the same town, Prague, in 1678, and was dedicated to Count Gerhard von Dernath, a military adviser to the Electorate of Saxony. The content of the two books is identical, and the differences between the two editions are in the engravings representing the coats of arms of the patrons and in the prefaces dedicated to them. The article also provides biographical data about the author, found from various historical sources, from which it is known that he was educated in Bulgaria in his hometown of Chiprovtsi, and then in Italy and Bohemia. At the end of the 17th and the beginning of the 18th century, Marko Peiachevich was one of the leaders of the Bulgarian Catholics. Photocopies of the cover page of the newly discovered book and of the page with the engraving with the coat of arms of Gerhard von Dernath are given in the appendix.